«The history cannot be rewritten, it can be added...» - Yu. Z. Kantor (Омский научный вестник: Серия "Общество. История. Современность")
Yulia Zorakhovna Kantor St. Petersburg historian, doctor of historical sciences, museologist and journalist, well-known expert on the history of international relations on the eve and during the Second World War, the author of the most complete and well-known biography of the red marshal M. N. Tukhachevsky. The interview was given by Yu. Z. Kantor to the member of the editorial board of the journal Omsk Scientific Bulletin. Series «Society. History. Modernity» D. I. Petin on August 13, 2018 in Omsk, in the Centre of Study the Civil War. It is dedicated to a wide range of current problems in the history of Russia: the development of the Arctic and museum business, international relations on the eve of the Second World War, the Civil War in Russia and the personalities of M. N. Tukhachevsky and A. V. Kolchak. The interview was finally edited by Yu. Z. Kantor in St. Petersburg in December 2018